The concept of art in the hermetic lyrics of V. Svidzinsky and V. Stus (Philological Studies: Scientific Bulletin of Kryvyi Rih State Pedagogical University, 2022)
The article considers Ukrainian hermetic lyrics as a variant of spiritual lyrics in the twentieth century and substantiates its conditionality with a modern worldview. It is emphasized that V. Stus continues the traditions of modernism of V. Svidzinsky. Individualism, nationalism and the desire for freedom of creative expression create an alternative to the totalitarian spiritual space. The study identifies the philosophical and aesthetic components of the concept of art of V. Svidzinsky and V. Stus; the originality of the poetic philosophy of artists, its influence on the formation of hermetic poetry is revealed; the evaluation of V. Svidzinsky’s work in the critical reception of V. Stus is investigated. It has been found that the concept of art was shaped by the realization that creativity remains the only way for an artist to create himself. The artist as a person reveals himself in the world with his own poetry. Poems became diaries of the soul, a story about their own inner life. The components of V. Svidzinsky’s poetic philosophy of “life-death” are determined: the balance of life by death, self-sacrificing individualism, smallness, concreteness, devotion to sensuality, not reason. V. Stus’s poetic philosophy of “self-fulfillment” is seen as a continuation of V. Svidzinsky’s imperative “lit up by itself ”. The evolution of V. Stus’ views on the understanding of the essence of art is traced: from the understanding of art as silence and silence to art as self-knowledge and to the concept of art-as-sacrum. It is proved that hermetic poetry expresses three semantic vectors of the concept of poet’s art: art-as-sacrum, art as silence, art as the work of becoming, as well as the concept of the artist as a wandering loner. The prospects of this research as further study of the intertextual field of Ukrainian hermetic poetry, study of variants of motives that open the way to knowledge of the world are determined.
Keywords: hermetic lyrics; modernism; the concept of art; “death”; “self-fulfillment”